Pengaruh Penambahan Filler Talc Terhadap Sifat Termal dan Massa Jenis Komposit Polipropilena/Masterbatch Black - Fitria Ika Aryanti; Dheandra Azani Maghfira (Jurnal Ilmiah Teknik Kimia, 2022)
Polypropylene/PP is one type of thermoplastic polymer that is widely used in everyday life. The use of fillers aims to reduce production costs and improve certain properties of the polymer matrix. This study aims to study the effect of adding talc as a filler on the physical and thermal properties of PP/masterbatch black (PP/MB Black) -based composites with percentages of 0, 5, 10, 15, and 20%. PP was mixed with 4% black MB Black and talc, then processed using injection molding. The composite product was then tested for thermal properties using Differential Scanning Colorimetry (DSC) and physical properties (density). The results showed that the addition of 20% of talc can increase the melting temperature with a melting temperature of 162.1°C and the lowest density of 0.908 g/cm3 without the addition of talc.